THE ROLE OF PARENTS IN BRINGING CHILDREN SCHOOL READINESS - Ferdy Tatu Ferdy; Rina Syafrida; Nur Rochimah (Journal of Early Childhood Education (JECE), 2023)
The study aims to investigate the role of parents in supporting a child's preparation for primary school. The study uses a qualitative approach, data collection is carried out through observations and interviews as well as documentation studies of 50 parents living in the city of Bekasi. Data analysis in this study was carried out using Miles and Huberman's approach. The findings of this study suggest that parents play a role in preparing the child's physical factors such as health, hygiene and balance before entering primary school. Parents also play a role in providing cognitive support so that the child is ready to solve problems that will be encountered on a daily basis. In terms of language, parents have a role to play in providing a language rich environment, providing opportunities to speak and listen appropriately and involving children in activities that support language development. Emotional readiness includes the child's ability to manage their own emotions, have intrinsic motivation and be able to cope with stress or anxiety. It is important to remember that a child's readiness to learn can vary greatly from individual to individual. Each child has a different rate of development and may require appropriate approaches to facilitate their readiness to learn.